Łódź 1914–1918. The Image of the City Experienced by War in the Light of Photographs from The State Archive in Łódź - Walkiewicz, Tomasz (Social consequences of war, 2024)
World War I left a clear mark in the history of Łódź. In November and December 1914, the Łódź Operation took place around the city, after which the German occupation began, lasting until November 1918. As a result of these events, the dynamic development of the „Polish Manchester” was stopped (the industry never reached the pre-1914 level of production) and the number of its inhabitants – including the suburbs – decreased from approximately 600,000 to 370,000.The image of the city’s war reality in the years 1914–1918 is presented by contemporary photographs, a large number of which have been preserved in the State Archive in Łódź, in archival groups: The iconographic collection of the State Archives in Łódź, the Collection of iconographic albums and the Local Assessment Committee in Łódź. They can be divided into two groups. The first includes photographs showing war losses: destruction of railway infrastructure, residential buildings, public buildings and factories, and requisitions made by the occupiers. The second one refers to the everyday existence of the civilian population and documents selected social problems: poverty, lack of fuel (wood, coal) and food, hunger and the fight of municipal services against infectious diseases.The photos of Michał Daszewski and other, mostly anonymous „war reporters” are a unique and extremely valuable historical source, providing objective and reliable information from the distant past. Photographs allow you to experience it firsthand. They show the everyday life of war in a way that is extremely suggestive and at the same time understandable to every viewer.